Microbiology of Tracheal Secretions: What to Expect with Children and Adolescents with Tracheostomies - El Cheikh, Mikhael R.; Barbosa, Juliane M.; Caixêta, Juliana A. S.; Avelino, Melissa A. G. (International Archives of Otorhinolaryngology, 2018)
Introduction People with tracheostomies exhibit a higher risk of colonization of the lower respiratory tract, acute tracheitis and pneumonia. Despite this, the culture of tracheal secretions is not a routine in most hospitals, and sometimes empiric therapy is based on personal experience, which is not an ideal situation.Objective To recognize the pathogens present in the tracheal secretions collected from people up to 18 years old with tracheostomies.Methods Prospective evaluation of patients under the age of 18 of a tertiary care hospital. A standardized questionnaire was completed, and tracheal secretion aspirates were sent for microbiological cultures and antibiograms.Results Twenty patients under 18 years of age were evaluated, 65% of whom were male. The microbiological culture was positive in 90% of the patients, and the most common microorganisms found were Pseudomonas aeruginosa (55.5%) and Staphylococcus aureus (27.7%).Discussion Tracheostomized children and adolescents have respiratory tracts colonized by pathogens, the most common of which is Pseudomonas aeruginosa. These patients must undergo tracheal secretion cultures, whether they present symptoms or not, to determine if there is a correlation between the colonization and the infections. This finding could guide the adequate treatment, avoiding the inappropriate use of antibiotics and indicating the better therapy in cases of laryngeal reconstruction.Conclusion In this sample, the culture of tracheal secretions was mainly positive, and the most common agent was P. aeruginosa. We suggest the routine access to Brazilian children and adolescents tracheal secretion cultures, which could help to make a profile of these children and guide the use of antibiotics.
Keywords: tracheostomy; children; adolescents; infection; bacteria; tracheal aspirate